Pengembangan Kesadaran Hukum dan HAM Dalam PKn (Studi Kasus Forum Pelajar Sadar Hukum dan HAM (FPSH HAM) Di Jawa Barat) - Eka Nur'Ala Hidayatin, - (2021)
At present law and human rights learning still centered in formal education in schools through Civics.The development of legal and human rights awareness can be done through an organization, namely Law and Human Rights Student Forum that play the role as citizenship education. This study aims to explore and analyze program activities in carrying out. The approach used in research is qualitative with case study method. The findings this study indicate that FPSH HAM has an effective role as citizenship education and legal education. Program activities according to the study of the scope of Civics and collaborates with various parties.